Learning al-Quran for children with disabilities - Salmihah Che Mud; Fariza Md Sham; Manisah Mohd Ali (Penerbit Universiti Kebangsaan Malaysia, 2021)
In Malaysia, children with disabilities (OKU) include hearing impairment, visual impairment, physical impairment, speech impairment, mental impairment, learning disabilities and various disabilities. Quranic learning for children with disabilities (OKU) is often neglected. This is because the community considers that children with disabilities are not required to study religion. Children with disabilities have various levels of disabilities and they have the ability to master the recitation of the Quran if given the opportunity. Therefore, the effort to provide opportunities for children with disabilities to learn religion such as reciting the Qur'an is fardh kifayah. In Malaysia, there are various methods of learning the Qur'an that have been used from ancient times until now such as the method of Iqra ', the method of Baghdadi and others. In fact, in recent times, the learning of the Quran for children with disabilities has gained focus due to the awareness of parents to teach the Quran to them. Therefore, this study aims to examine the methods of learning the Qur'an used to children with disabilities in Malaysia and the challenges faced in the process of learning the Qur'an. The research method used in this study is document analysis based on previous studies and research through journals and books related to the discussion on the learning of the Quran for children with disabilities. The results of the study found that there are three methods of learning the Quran used for disabilities in Malaysia, namely the method of Fakih, the method of Abahata al-Jabari and the method of skin sensitivity for visual impairment. However, in an effort to implement Quranic learning for children with disabilities, there are challenges faced, namely experienced teachers, children's interest in learning the Quran, controlling the emotions and behavior of children with disabilities as well as space and environmental problems. The implication of the study is to identify the existing methods of learning the Qur'an that can be used as a guide by parents, teachers and preachers in teaching the Qur'an to children with disabilities. In addition, agencies that manage children with disabilities may adopt the most appropriate method according to the type of disability.